FEATURES OF THE USE OF WORDS IN KYRGYZ COMPLAINT-SONGS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the linguistic nature of Kyrgyz complaint-songs in the linguistic and communication aspect, the peculiarities of using words in complaint-songs. Based on specific factual materials, issues such as the main words used in such songs and their artistic semantic features, the communicative, semantic and stylistic functions that they perform in the text, the relation of keywords to the expression of content as a special artistic detail were investigated.
Keywords: the theme of falling in love, the content of sadness, the main words, a special artistic detail, a lyrical hero, artistic expression, comparison, logical emphasis, simple words that are conve- nient for expressing meaning